2021
DOI: 10.20961/placentum.v9i3.54667
|View full text |Cite
|
Sign up to set email alerts
|

Corelation of Stress Levels During Covid-19 Pandemic and Menstrual Cycle of Diploma IV Midwifery Student of Sebelas Maret University

Abstract: <p>The pandemic period caused by the SARS-CoV2 virus is a global problem that has an impact on the community, including students. Task load and online learning systems are factors that cause students to experience stress, this can be one of the causes of disruption of the menstrual cycle. Changes in the menstrual cycle is a health problem for some women. This study aims to link stress levels during the coronavirus disease 19 pandemic to the menstrual cycle of UNS Diploma IV Midwifery students.This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Thus, age, education, maturity, and work will affect women's psychological condition during the COVID-19 pandemic. In addition, research by Nareswari et al (2021) showed no significant relationship between stress levels during the Covid-19 pandemic and changes in the menstrual cycle (Nareswari et al, 2021).…”
Section: Introductionmentioning
confidence: 96%
“…Thus, age, education, maturity, and work will affect women's psychological condition during the COVID-19 pandemic. In addition, research by Nareswari et al (2021) showed no significant relationship between stress levels during the Covid-19 pandemic and changes in the menstrual cycle (Nareswari et al, 2021).…”
Section: Introductionmentioning
confidence: 96%